Insurance Denials in Reduction Mammaplasty: How Can We Serve Our Patients Better?. Issue 2 (August 2020) - Boukovalas, Stefanos; Boson, Alexis L.; Padilla, Pablo L.; Sljivich, Michaela; Tran, Jacquelynn P.; Spratt, Heidi; Phillips, Linda G.
Abstract : Background: Reduction mammaplasty is the standard of care for symptomatic macromastia. The process of requesting insurance coverage for reduction mammaplasty is cumbersome and potentially controversial, and insurance policies vary significantly. The goal of our analysis is to identify trends in insurance coverage rates, assess for the presence of disparities, and propose ways to increase chances of successful preauthorization. Methods: The authors performed a retrospective review of preauthorizations for reduction mammaplasty at a single institution from 2012 to 2017. Insurance company names were deidentified. Preauthorization denial rates were assessed by year, insurance carrier, and reason for denial. Multiple regression analysis was performed to identify predictors for predetermination denial by insurance companies. Results: Among 295 preauthorizations, 212 were approved (72 percent) and 83 were denied (28 percent), among which 18 were appealed, 13 successfully. Rates of insurance denials have been increasing steadily, from 18 percent to 41 percent. Medicaid had the lowest denial rates (9.3 percent), whereas private carriers denials ranged from 21.4 to 62.1 percent. In terms of reason for denial, 30 percent were because of contract exclusion, 39 percent were because of inadequate documentation or not meeting medical criteria, and 12 percent were because of inadequate predicted resection weight. Certain private insurance carriers were the only independent predictors of predetermination denial. Conclusions: Rate of preauthorization denials is high and has been increasing steadily. Insurance criteria remain arbitrary. A proper documentation and appeal process by the plastic surgeon may improve rates of insurance approval. Although resection weight does not correlate with symptom relief, predicted breast tissue resection weight continues to be critical for insurance approval. Abstract : Supplemental Digital Content is available in the text.